Experience to date with CFTR modulators during pregnancy and breastfeeding in the British Columbia Cystic Fibrosis clinic. (2022) - Goodwin, Jodi; Quon, Bradley S.; Wilcox, Pearce G.
Abstract: The introduction and rapid uptake of CFTR modulator therapy, in addition to other treatments, has significantly increased life expectancy in CF and provided more women the opportunity to consider and successfully be managed throughout pregnancy. There is however limited evidence to guide patient management and enable informed decision making. Here we report the experience to date from a large multidisciplinary Cystic Fibrosis quaternary referral center in managing patients on CFTR modulators in the peri- and post-partum periods. While women in this case series were advised to discontinue CFTR modulators during pregnancy, they would likely receive a very different message today.